2002
DOI: 10.1111/j.1095-8649.2002.tb02401.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and glucose responses in juvenile brown trout subjected to a fluctuating flow regime in an artificial stream

Abstract: In an artificial stream channel, wild 1 year old brown trout Salmo trutta were exposed to fluctuations in flow and water level to simulate hydro-peaking conditions downstream of a hydropower installation. Blood plasma cortisol concentrations reached a maximum of 59·4 35·3 ng ml 1 (mean 95% CL) 2 h after the end of down-ramping. Return to the pre-exposure cortisol level was achieved within 6 h. When subjected to daily cyclical fluctuations over 7 days, plasma cortisol levels were significantly elevated (61·3 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 29 publications
3
70
0
2
Order By: Relevance
“…The effects of perceived predation risk on different stress responses probably vary among species, and, in particular, effects on cortisol levels may be small in brown trout (Lepage et al, 2001). Nonetheless, individual plasma cortisol concentrations varied greatly, and were all high compared to those in other studies of unstressed or mildly stressed brown trout (Flodmark et al, 2002;Brelin et al, 2005). Mean cortisol concentration was instead roughly the same as those reported for trout after being subjected to handling or confinement stress (Norris et al, 1999;Ruane et al, 1999;Barton, 2000).…”
Section: Discussionmentioning
confidence: 64%
“…The effects of perceived predation risk on different stress responses probably vary among species, and, in particular, effects on cortisol levels may be small in brown trout (Lepage et al, 2001). Nonetheless, individual plasma cortisol concentrations varied greatly, and were all high compared to those in other studies of unstressed or mildly stressed brown trout (Flodmark et al, 2002;Brelin et al, 2005). Mean cortisol concentration was instead roughly the same as those reported for trout after being subjected to handling or confinement stress (Norris et al, 1999;Ruane et al, 1999;Barton, 2000).…”
Section: Discussionmentioning
confidence: 64%
“…Our experiments did not measure stress, but it has been shown that juvenile brown trout exposed to a fluctuating flow regime quickly recover from this artificial stressor and that their blood cortisol levels normalise already after 6 h after the first low flow stage [22]. When measuring blood cortisol after consecutive days of fluctuating flow and water levels, [22] did not find differences in cortisol levels between the control and treatment fish.…”
Section: Discussionmentioning
confidence: 85%
“…When measuring blood cortisol after consecutive days of fluctuating flow and water levels, [22] did not find differences in cortisol levels between the control and treatment fish. Although fish showed an initial stress-response to the changes in water flow, the effect was only short lived and brown trout became accustomed to the stressor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Άλλες παράμετροι, οι οποίες είναι ιδιαίτερα σημαντικές σε ορισμένες εκτροφές, όπως οι πεστροφοκαλλιέργειες, είναι η στάθμη και η ροή του νερού εκτροφής, αφού οποιαδήποτε αλλαγή τους μπορεί να αποτελέσει αίτιο πρόκλησης στρες (Flodmark et al 2002).…”
Section: β2 συνθήκες εκτροφήςunclassified